Discussion of Agile Software Development Methodology and its Relevance to Software Engineering - Amitkumar Dudhat; Muhammad Ali Abbasi (ADI Journal on Recent Innovation, 2021)
Agile Software Development Methodology is a lesser-known and infrequently utilized methodology in academia. In reality, though, content developer software practitioners frequently employ this technique. This journal was created to give readers an overview of agile techniques and their use at various stages of software development in general.